Johan Béla és a modern magyar közegészségügy kiépítése - Cora Zoltán (Középkori és Kora Újkori Magyar Történeti Tanszék Szeged, 2023)
The relationship between the Horthy era (1920–1944) and the communist era shows continuities if it is examined from a social historical perspective. The paper contributes to the reinterpretation of these relations by looking at Hungarian health care in the 1930s and 1940s with a focus on the relationship between international transfers and path dependency in forging health care reforms. I argue that the achievements communists regarded as inventions of socialism in health care and the welfare state had already been developed thoroughly in the 1930s and 1940s. It was only because of the strict wartime budget of the early 1940s that these welfare reforms had not been realised. With the help of internal affairs documents, essays on health care, and official statistics records in the National Archives of Hungary and the Semmelweis Library and Archives of Medical History in Budapest as well as press material, I demonstrate that, even if communists depicted the interwar period as “fascist and imperialist”, the health care system of the so-called “productive social policy” showed continuities. Moreover, social policy makers of the 1930s and early 1940s, such as Béla Johan, Ferenc Keresztes-Fischer and Béla Kovrig, also designed welfare and health care reforms for the post-war period by both developing already existing Hungarian programmes and selectively adapting foreign welfare models (American management principles, the Alsace scheme, and the Beveridge Plan). The study investigates Hungarian health care in view of the theory of path dependency and the macrohistorical convergence thesis developed by Béla Tomka (on the question of East-West convergence). It is within this framework that the paper addresses the issue of health care transfers to better understand the development of 20th -century European health care systems by identifying similarities and differences in their development as well as to speculate on the trajectory of various political solutions to social challenges, including health care.
Keywords: Bölcsészettudományok; Történettudomány és régészet